METODE SYAWIR SEBAGAI STRATEGI PEMBELAJARAN FIQIH UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SANTRI PESANTREN MAHASISWA AL-HIKAM: The Syawir Method as a Fiqh Learning Strategy to Improve the Critical Thinking Skills of Students at the Al-Hikam Student Boarding School - Muthmainnah; Rokhman, Imam Athoir (STAI Ma'had Aly Al-Hikam Malang, 2025)
Critical thinking is one of the important things for the students of the Pesantren Mahasiswa Al-Hikam Malang to have, especially in learning fiqh, because fiqh is the knowledge of shari'ah amaliyah law obtained through ijtihad with a critical thinking process in an environment that is engineered in such a way as to become a Learning Society. This research uses a qualitative approach, a case study type of research, and data mining using observation, interviews, and documentation. Data collection, data presentation, and conclusion are the data analysis techniques used in this research. The research results show that: (1) The implementation of the Syawir method includes good planning, measurable implementation, and evaluation. (2) The supporting factors are the provision of good infrastructure, asatidz, and support from various participant backgrounds from Salaf students and alumni. Meanwhile, the inhibiting factors are the lack of activity and self-confidence of some students, as well as the limited time for carrying out Syawir.